Analysis of the Meaning of Instagram @unmermadiun Content in Building the Meaning of Education in FISIP Students at Merdeka Madiun University - Offy Ayuningtiyas; Zulin Nurchayati; Nunik Hariyani (IKIP Budi Utomo Malang, 2020)
The purpose of this study is to examine the acceptance of followers of the Instagram @unmermadiun account for content (photos, videos, texts) in building the meaning of education on Instagram social media. The paradigm of this research is constructivism with the type of qualitative research. Data were collected using in-depth interviews, observation and documentation. Technical data analyst with the stages of data collection, data selection, data presentation and conclusion drawing. The theory used is Reception Theory Analysis by Stuart Hall. The informants of this study were fourteen people who followed the Instagram account @unmermadiun with different backgrounds. The results showed that three out of ten informants were in the dominant position, four were in the negotiating position, and the informant with the opposite position was not found. (1) In a dominant position, the informants interpret that the contents of the Instagram account @unmermadiun as a goal to build educational meaning, so they also like and agree with it and apply the thoughts conveyed by the account. (2) In a negotiating position, the informant has meaning and is reluctant to take it for granted, understanding the mind at first is important to them. Keywords : Receptions, Social media, Instagram